2017
DOI: 10.1007/978-3-319-42745-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Why and How Does Shared Language Affect Subsidiary Knowledge Inflows? A Social Identity Perspective

Abstract: Copyright and moral rights to this thesis/research project are retained by the author and/or other copyright owners. The work is supplied on the understanding that any use for commercial gain is strictly forbidden. A copy may be downloaded for personal, non-commercial, research or study without prior permission and without charge. Any use of the thesis/research project for private study or research must be properly acknowledged with reference to the work's full bibliographic details.This thesis/research projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 96 publications
0
40
0
3
Order By: Relevance
“…Specifically, first, leaders’ use of meaning-making language emphasizes organizational values and aligns the personal goals of employees with those of the organization. The shared values and purpose may bind employees together and enhance employee connection with the organization, thus satisfying the psychological need for relatedness ( Mayfield & Mayfield, 2018 ; Reiche et al, 2017 ). Second, leaders’ use of empathetic language sends message of empathy, compassion, care, and support ( Mayfield & Mayfield, 2018 ), which makes employees feel they are not alone facing various challenges during the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, first, leaders’ use of meaning-making language emphasizes organizational values and aligns the personal goals of employees with those of the organization. The shared values and purpose may bind employees together and enhance employee connection with the organization, thus satisfying the psychological need for relatedness ( Mayfield & Mayfield, 2018 ; Reiche et al, 2017 ). Second, leaders’ use of empathetic language sends message of empathy, compassion, care, and support ( Mayfield & Mayfield, 2018 ), which makes employees feel they are not alone facing various challenges during the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An alternative way to augment subsidiaries’ absorptive capacity might be recruitment, as this study suggests. By recruiting individuals who have professional expertise that subsidiaries demand or lack, subsidiaries can reinforce and strengthen their absorptive capacity, which increases the degree of knowledge base overlap between subsidiaries and the parent firm and promotes knowledge transfer (Barkema and Drogendijk, 2007; Reiche et al , 2015). In addition to recruiting individuals who have higher professional expertise, the results of this study indicated the importance of language and intercultural skills in cross-border settings.…”
Section: Discussionmentioning
confidence: 99%
“…a subsidiary) have established their knowledge bases separately. These two organizations might have distinct knowledge bases that do not have sufficient overlap (Reiche et al , 2015). To transfer knowledge, they must share a certain level of common ground where knowledge can flow in the post-acquisition stage (Reiche et al , 2015; Sarala and Vaara, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discourses used when describing RP show how they become a part of, and therefore a lasting fixture inside schools. Reiche et al (2017) highlight that a shared language can have significant impact on the knowledge uptake inside institutions and therefore the identity of those comparing them.…”
Section: Formation Of a Shared Identitymentioning
confidence: 99%